2016
DOI: 10.4238/gmr.15027941
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional silencing of the SGE1 gene induced by a dsRNA hairpin in Fusarium oxysporum f. sp cubense, the causal agent of Panama disease

Abstract: ABSTRACT. Fusarium oxysporum f. sp cubense (Foc), the causal agent of Panama disease, is responsible for economic losses in banana crops worldwide. The identification of genes that effectively act on pathogenicity and/or virulence may contribute to the development of different strategies for disease control and the production of resistant plants. The objective of the current study was to analyze the importance of SGE1 gene expression in Foc virulence through post-transcriptional silencing using a double-strand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Homologs of SGE1 in Foc tropical race 4 (Foc TR4) and race 1 are also required for regulation of virulence in banana roots. An in planta RNAi (siRNA) approach using host‐induced silencing of the SGE1 gene of Foc TR4 in banana plants confirmed that the SGE1 gene is directly involved in the virulence of Foc (Fernandes et al, 2016). In other Fusarium species, such as F. graminearum and F. verticillioides , Sge1 is thought to regulate the expression of effectors and secondary metabolite biosynthetic genes (Brown et al, 2014; Jonkers et al, 2012).…”
Section: Transcriptional Regulation Of Direct Virulence Factors In F Oxysporum Including Effectors Cwdes and Mycotoxinsmentioning
confidence: 94%
“…Homologs of SGE1 in Foc tropical race 4 (Foc TR4) and race 1 are also required for regulation of virulence in banana roots. An in planta RNAi (siRNA) approach using host‐induced silencing of the SGE1 gene of Foc TR4 in banana plants confirmed that the SGE1 gene is directly involved in the virulence of Foc (Fernandes et al, 2016). In other Fusarium species, such as F. graminearum and F. verticillioides , Sge1 is thought to regulate the expression of effectors and secondary metabolite biosynthetic genes (Brown et al, 2014; Jonkers et al, 2012).…”
Section: Transcriptional Regulation Of Direct Virulence Factors In F Oxysporum Including Effectors Cwdes and Mycotoxinsmentioning
confidence: 94%
“…In addition, conidiation was reduced and subsequent studies in the banana pathovar F. oxysporum f. sp. cubense through gene knockout and RNAi (Fernandes et al, 2016) identified similar regulatory roles for Sge1 in these contexts. For other members of the Fusarium genus, Gti1…”
Section: The Gti1/pac2 Familymentioning
confidence: 94%
“…oxysporum f. sp. cubense through gene knockout (Hou et al., 2018) and RNAi (Fernandes et al., 2016) identified similar regulatory roles for Sge1 in these contexts. For other members of the Fusarium genus, Gti1 orthologues are global regulators of effector gene expression or SM biosynthesis (Brown et al., 2014; Jonkers et al., 2012; Michielse et al., 2015).…”
Section: Tfs and Their Role In Virulence In Plant‐pathogenic Fungimentioning
confidence: 96%
“…In Fusarium oxysporum f.sp. cubense tropical race 4 (Foc TR4) and race 1, Sge1 is required for virulence in banana roots (Fernandes et al 2016). In the present study, during Fox R1 infection, 11.4 log2Fold expression of gene encoding TF Sge1 was recorded.…”
Section: Pathogenicity and Virulence Genes Of Fox R1mentioning
confidence: 99%